Avaliação da anestesia peridural e do bloqueio perineural dos nervos ciático e femoral com lidocaína 2% em cães anestesiados pelo isoflurano e submetidos à cirurgia de correção de ruptura de ligamento cruzado cranial - Cardoso, Guilherme Schiess [UNESP] (2015)
The lumbosacral plexus innervates the pelvic limb in dogs. The femoral and sciatic nerves are the main branches originated from lumbar and sacral plexus, respectively. Peripheral nerve blocks of femoral and sciatic has been reported as an alternative to epidural anesthesia for perioperative pain management.This study aimed to compare the perioperative efficacy of epidural and combined femoral and sciatic nerve blocks, carried out with or without peripheral nerve stimulator assistance. Lidocaine was adminitraded to 29 dogs undergoing stifle surgery, randomly assigned into three treatments: PD (n = 10): epidural; PN (n = 10) combined femoral and sciatic nerve blocks performed with peripheral nerve stimulator guidance; RA (n = 9): femoral and sciatic nerve blockade using anatomical landmarks. Heart rate (HR), respiratory rate (HR), systolic blood pressure (SBP), mean arterial pressure (MAP), and rectal temperature (Tº) were monitored. Fentanyl (3.0 mcg.kg-1 - IV) was given if it was observed increase in HR, SBP or MAP (more than 20% of baselines values). Pain and sedation were evaluated in the moments M1, M2, M4, M6, M8, M10, M12 and M24 after surgery. Pain assessment was performed using a Glasgow modified scales (GMS), scale of the Colorado State University (CSU) and Visual Analog Scale (VAS).If pain scores were higher than 3.33 in GMS or VAS, or higher than 2 in CSU morphine (0.5 mg.kg-1 - IM) was administrated. Statistical analysis was performed by analysis of variance (ANOVA) for the parametric variables. To compare treatments we used the Kruskal-Wallis test, and for the moments the Friedman test. The backlog of rescues was adjusted in a Logistic regression for each treatment. A 5% significance level was adopted. Epidural abolished the need for intraoperative rescue analgesia, differing significantly from the PN and RA treatments that need rescue during the surgical procedure. RA required more trans-operative analgesics than PN, ...